FACTORS AFFECTING ADHERENCE TO RECOMMENDED MEDICATIONS AMONG PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) IN A SELECTED TEACHING HOSPITAL, SRI LANKA - Dassanayaka, I.M.M.; Dayananda, K.K.V.P.; Amarasekara, Thamara D. (International Journal of Research -GRANTHAALAYAH, 2019)
Background: This study was conducted to determine the prevalence of adherence and factors affecting adherence to recommended medications among patients with COPD in a selected teaching hospital, Sri Lanka. Method: A descriptive cross-sectional design was used among conveniently selected (n=184) participants who attended to the Colombo South Teaching Hospital, Sri Lanka. Data were collected using a pre-tested (n=10) interviewer-administered questionnaire and Morisky Green Levine Scale from January to March 2019. Results: Most of the participants were male (108, 58.7%) and above 65 years old (108, 58.7%). Among all participants, 121 (65.8%) adhered to the recommended medications for COPD, and 63 participants (34.2%) were non-adhered. Demographic factors were not associated with adherence. Number of prescribed respiratory drug classes, number of respiratory medication on the last prescription, number of doses per day, vaccination (pneumococcal, influenza), using an electronic device to remember the time of administering medicine, (p<0.05) were significantly associated with adherence. According to the binary logistic regression analysis, clear and understandable written instructions in dispensing label (p<0.05) were significantly associated with adherence. Conclusions: Most of the participants adhered to the recommended medications for COPD. Health education interventions might enhance the sustainability of adherence to recommended medication among patients with COPD.